Pelatihan Pembuatan Bahan Ajar Menggunakan Aplikasi Flipbook untuk Menunjang Pembelajaran Daring Bagi Guru-guru MGMP IPS Kabupaten Lampung Selatan - Imanita, Myristica; Insani, Marzius; Rachmedita, Valensy (Suluah Bendang: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2022)
During the COVID-19 pandemic, the learning system underwent significant changes. Teachers as educators must immediately adapt to the conditions so that education continues to run well. Teachers inevitably have to be innovate and creative so that learning objectives are achieved even though the learning is done online. However, in the implementation of online learning, there are still some obstacles or problems. This condition is also experienced by social studies teachers in South Lampung Regency. One of the efforts to maximize online learning is to maximize the use of teaching materials. Making teaching materials using the Flipbook Application or digital books is considered relevant to current conditions. In addition to being cheap and efficient, in this application, teachers can design their own learning materials according to achievement indicators, student needs and student characteristics so that they are more effective and on target. This service uses counseling and training methods. The resulting output target is the ability of MGMP teachers in South Lampung Regency to design basic materials in the form of modules with flipbook applicatioKey words: Keywords: teaching materials, flipbook applications, innovation and creativity